Noninvasive measurement of regional pulse wave velocity in human ascending aorta with ultrasound imaging: an in-vivo feasibility study. Issue 10 (October 2016) - Huang, Chengwu; Guo, Dong; Lan, Feng; Zhang, Hongjia; Luo, Jianwen
Abstract : Objectives: Accurate and noninvasive techniques for measurement of local/regional pulse wave velocity (PWV), instead of global PWV, is desired for quantifying localized arterial stiffness and improving cardiovascular disease assessment. This study aimed at investigating the feasibility of regional PWV measurement in human ascending aorta in vivo using an ultrasound-based technique. Methods: Proximal ascending aortas of 76 healthy patients (23–71 years) were scanned with transthoracic echocardiography in parasternal long-axis view, and ultrasound radiofrequency data were acquired in a high temporal resolution (∼404 Hz). The PWV was derived from the determination of arrival times and identification of travel distances. Both PWVs in early systolic phase (PWVsf ; pulse wave velocity measured using the systolic foot as characteristic time point) and late systolic phase (PWVdn ; pulse wave velocity measured using the dicrotic notch as characteristic time point) were obtained. Results: The PWVsf and PWVdn were 4.58 ± 1.38 and 6.51 ± 1.90 m/s, respectively, and both were correlated with age ( r  = 0.30, P  = 0.02 and r  = 0.71, P  < 0.0001). The measurements were reproducible, and PWVdn showed significant correlation with aortic diameter ( r  = 0.53, P  < 0.0001), relative distension ( r  = −0.44, P  = 0.0002), and local PWV derived from Bramwell–Hill equation ( r  = 35, P  = 0.004). The PWV difference (PWVdn  − PWVsf ) reflected aortic stiffness change within cardiac cycle from early systole to late systole and was also correlated with age ( r  = 0.50, P  < 0.0001). Conclusion: The feasibility of ascending aortic PWV measurement using ultrasound imaging was illustrated in vivo, suggesting the potential of the technique in characterization of regional aortic stiffness and assessment of aortic diseases. Abstract : Supplemental Digital Content is available in the text